2009
DOI: 10.4081/gh.2009.208
|View full text |Cite
|
Sign up to set email alerts
|

Spatial assessment of animal manure spreading and groundwater nitrate pollution

Abstract: Abstract. Nitrate concentration in groundwater has frequently been linked to non-point pollution. At the same time the existence of intensive agriculture and extremely intensive livestock activity increases the potential for nitrate pollution in shallow groundwater. Nitrate used in agriculture could cause adverse effects on human and animal health. In order to evaluate the groundwater nitrate pollution, and how it might evolve in time, it is essential to develop control systems and to improve policies and ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…In intensive agriculture and livestock areas, in particular where sandy soils are prevalent, excess of irrigation and fertilization may lead to pollution of groundwater. Similar findings in adjacent areas with intensive buffalo breeding were obtained by Infascelli et al [55].…”
Section: Nitrogen Leaching and Winepic Simulationsupporting
confidence: 79%
See 1 more Smart Citation
“…In intensive agriculture and livestock areas, in particular where sandy soils are prevalent, excess of irrigation and fertilization may lead to pollution of groundwater. Similar findings in adjacent areas with intensive buffalo breeding were obtained by Infascelli et al [55].…”
Section: Nitrogen Leaching and Winepic Simulationsupporting
confidence: 79%
“…In intensive agriculture and livestock areas, in particular where sandy soils are prevalent, excess of irrigation and fertilization may lead to pollution of groundwater. Similar findings in adjacent areas with intensive buffalo breeding were obtained by Infascelli et al [55]. Figure 3 shows the results of the WinEPIC simulation of the NO3 − concentration in soil water for two complete annual crop cycles, together with the values of measured NO3 − concentration in the lysimeters; during the second corn crop no samples were considered.…”
Section: Nitrogen Leaching and Winepic Simulationsupporting
confidence: 66%
“…The number of heads per livestock herd is high in some areas; the ratio of heads per ha of usable agricultural surface exceeds 10 head/ha (Infascelli et al, 2010). Infascelli et al (2009) found a discrepancy between modelling of nitrate leaching and monitoring of the groundwater. Also, no spatial correlation between nitrogen production in livestock farms and nitrate concentration in groundwater was found (Infascelli et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Without the hierarchical monitoring via helicopter, prior coastal monitoring for this region limited its focus to pollution from the largest channels, including the Volturno, and another large channel further north, called the Garigliano [36][37][38][39]. Due to the larger discharge plumes from these rivers, they have been considered to be the principal cause of water quality impairment.…”
Section: Variablesmentioning
confidence: 99%